Circular Letters as Social Engineering: The Authority of the East Java Provincial Government in Preventing Child Marriage - Barorotun Niswah Nur Hamidah; Arlinda Nur Azizah; Sharifah Nur Ilham Syed Ali (Universitas Negeri Surabaya, 2025)
This research examines the authority of East Java's provincial government in issuing a circular letter as a tool for social engineering to mitigate child marriages. Using normative-prescriptive methods, the study incorporates a conceptual and statutory approach with primary, secondary, and tertiary legal materials. The findings indicate that the circular letter serves as a policy instrument influencing public behavior to reduce child marriages. However, its substance, which binds external parties, suggests that a formal legal regulation, such as a regional or gubernatorial regulation, would be more appropriate. The study recommends the development of comprehensive legal frameworks harmonized across provincial and municipal levels, emphasizing the critical role of collaboration in addressing child marriage through legally binding and coordinated efforts. This approach aligns with the objective of safeguarding children's rights while ensuring effective policy implementation across the region.